Revitalization Of Passive Village Unit Cooperatives In Improving Digital-Based Independent Villages - Hariyono, Hariyono; Zuhroh, Siti; Nuraini, Rini; Almahdali, Fadila; Desri , Syuryatman (Universitas Pahlawan Tuanku Tambusai, 2024)
The importance of the existence of Village Unit Cooperatives in rural areas in order to protect rural communities so that they avoid loans that have large interest rates, limited capital in developing businesses, and several other things that become obstacles to the development of rural community businesses made the author take the initiative to carry out community service in the context of revitalizing the Sumber Pangan Nganjuk Village Unit Cooperative, the Usaha Makmur Talise Village Unit Cooperative, the Subur Sutiyana Farmers Cooperative, South Kalimantan, and the Murni Village Unit Cooperative in West Sumatra, which were passive and not well managed with the following stages. In the end, the author hopes that with an active KUD, the village can become independent and create an independent, digital-based village. The results in this article show 1. The initial stages carried out are major revitalization by regenerating unproductive human resources by prioritizing productive and superior human resources, collaborating with village officials, tidying up the administration and secretariat, and creating realistic minor programs to be implemented in the near future. 2. The second stage is major revitalization if the minor program has been running to spread its wings by requesting funding from the local regional government and collaborating with third parties who have low interest rates, including financial institutions, banking, fintech, and so on. 3. If minor and major revitalization has been carried out then the achievements of an independent village can easily be achieved. In the end, the village only needs to upgrade the form of service to digital. In this way, a digital-based independent village has been achieved.